Knowledge, Attitude and Practices Regarding Simplified Kundalini Yoga Among College Students in Tamilnadu: Life Sciences -Physiology - Periasamy, Panneerselvam; Suganthi, Vajiravelu; Gunasekaran, Sasikala (International Journal of Life Science and Pharma Research, 2022)
Simplified Kundalini Yoga (SKY) is a physical, mental and spiritual discipline for developing strength, awareness, character, and consciousness. Simplified physical exercises, simplified Kundalini meditation, Kayakalpa practice, and introspection are its components. Health professionals consider yoga for skeletal symptoms, followed by psychological and physical ailments. Stress is a common issue for college students during their undergraduate studies. Short-term yoga has been proven to help pupils feel less stressed. The purpose of this study was to evaluate college students' knowledge, attitudes and practice of (KAP) Simplified Kundalini Yoga. A secondary objective was to compare KAP among medical, paramedical and non-medical students in Tamilnadu, India. A cross-sectional web-based online survey among the medical, paramedical and non-medical students were conducted. A semi-structured questionnaire using a non-probability volunteers sampling technique was used in this study. There were 323 responses in total: 101 medical students (40 males and 61 females), 100 paramedical students (19 males and 81 females), and 122 non-medical students (1 male and 121 females). All participants were given a pre-tested questionnaire about their awareness, attitudes, and practices related to SKY. The data collected were entered in MS Excel and presented in tables and graphs. Significant results were subjected to tests of significance like the Chisquare test at a 5% level of significance. In general, only 6.5% of them have adequate knowledge scores, 26 % of them have a good level of attitude score, and 8.7% of them have a good level of practice score. More than 80-90% of students lack knowledge, attitude and practice of SKY. Reasons for not taking up yoga were mainly lack of interest, laziness and poor time management. The study concluded that students have a positive outlook towards simplified Kundalini yoga but need motivation.